PENGARUH MOTIVASI BELAJAR SISWA TERHADAP HASIL BELAJAR GEOGRAFI DI KELAS X IPS SMAN 1 SUNGAI PUAR KABUPATEN AGAM - sayoga, Nanda bhakti; Surtani, Surtani (JURNAL BUANA, 2023)
This study aims to obtain, process, analyze, and discuss data on the Effect of Student Learning Motivation on Student Geography Learning Outcomes in Class X Social Sciences at SMAN 1 Sungai Puar, Agam Regency, West Sumatra Province, for the academic year 2021/2022. The method in this study is a quantitative method with the type of correlational research. The population in this study were all students of class X IPS 1,2, and 3 as many as 82 people. Sampling was taken by total sampling with a total sample of 82 people. The instrument used is a questionnaire. Data analysis used in 2 ways, namely: (1) descriptive statistical analysis, (2) Regression analysis. The results: There is a significant and positive relationship between students' learning motivation and learning outcomes of Geography in class X Social Sciences SMAN 1 Sungai Puar, Agam Regency, with an rxy correlation coefficient of 0.322 which indicates a low relationship between students' learning motivation and students' learning outcomes of Geography in class X IPS SMAN 1 Sungai Puar, Agam Regency.